(untitled) (Iranian Journal of Kidney Diseases, 2019)
Introduction. The aim of current study is investigation of theimpact of serum FGF23 levels on blood pressure of patients withend-stage renal disease (ESRD) undergoing hemodialysis.Methods. Based on registry, 68 patients who underwent hemodialysis(HD) in the dialysis center of Shahid Beheshti hospital, Anzali,north of Iran, from April 2016 to May 2017 were enrolled. Enzyme-Linked ImmunoSorbent Assay (ELISA) was used to determineserum FGF23 levels. 24 hours blood pressure monitoring method,AMBB, was used to monitor the mean arterial pressure of patients.Spearman related analysis method was used to statistically analyzethe correlation of serum FGF23 level with mean arterial pressure,age, HD duration, kt/v, URR weight gaining, cause of ESRD, andthe mentioned laboratory parameters.Results. Serum FGF23 levels of ESRD patients were not significantlyrelated to age, time of HD and gaining weight. Furthermore,these parameters were not related to blood pressure. However,FGF23 expression levels in serum were positively correlated withphosphorous and calcium- phosphorous. The mentioned laboratoryparameters had no significant correlation with 24 hours bloodpressure changes. Meanwhile, the minimum diastolic pressureand intact parathyroid hormone (iPTH) level showed a significantdirect linear correlation.Conclusion. We suggest that understanding relationship betweenphosphate, FGF23 and cardiovascular disease can be applied intargeted phosphate-based treatment. Kidney failure and the nondippercondition may be highly related to one another and leadto ESRD. Therefore, a special investment in controlling bloodpressure and examining it with a tool such as ABPM can greatlyhelp patients to progress effectively.